Retrospective Analysis of the Efficacy and Safety of Ultrasound-Guided Radiofrequency Ablation in the Treatment of Papillary Thyroid Microcarcinoma: A Follow-Up Study of Continuous Postoperative Surveillance and Large-Sample Data - Gongli Zhou; Xuefeng Zhang; Ke Xu; Beibei Zhang; Ruiqing Su; Tingting Cai; Wei Zhao; Feng Li (International Journal of Endocrinology)
Objective. To retrospectively evaluate the efficacy and safety of ultrasound-guided radiofrequency ablation (RFA) in the treatment of papillary thyroid microcarcinoma (PTMC) through a follow-up study of continuous postoperative surveillance and large-sample data. Methods. The efficacy of ultrasound-guided RFA was evaluated by measuring the tumor volume reduction rate (VRR), tumor disappearance rate, and disease progression in 358 patients with low-risk unifocal PTMC who underwent ultrasound-guided RFA at Hangzhou Weja Hospital, while the safety was evaluated by measuring their complications. Results. The VRR was −745.69 ± 1012.69 (%), −150.35 ± 395.5 (%), 46.47 ± 138.74 (%), 92.95 ± 27.88 (%), 97.78 ± 10.99 (%), and 99.27 ± 3.82 (%), respectively, at 1, 3, 6, 12, 18, and 24 months after RFA. The corresponding tumor disappearance rate was 1.68%, 9.78%, 43.85%, 82.68%, 92.59%, and 95.63%, respectively. No local recurrence, new tumors, lymph node metastasis, distant metastasis, and deaths caused by recurrent/metastatic PTMC were found at the last follow-up. Except for 3 cases (0.84%) with thickening or hoarseness of voice and 3 cases (0.84%) with coughing during drinking water, no other complications were found. Conclusions. Ultrasound-guided RFA has good efficacy and safety for the treatment of low-risk unifocal PTMC and can be promoted for use in patients who meet the required indications.